IGFBP3 deposited in the human umbilical cord mesenchymal stem cell‐secreted extracellular matrix promotes bone formation. Issue 8 (1st March 2018) - Deng, Moyuan; Luo, Keyu; Hou, Tianyong; Luo, Fei; Xie, Zhao; Zhang, Zehua; Yang, Aijun; Yu, Bo; Yi, Shaoxuan; Tan, Jiulin; Dong, Shiwu; Xu, Jianzhong
Abstract : The extracellular matrix (ECM) contains rich biological cues for cell recruitment, proliferationm, and even differentiation. The osteoinductive potential of scaffolds could be enhanced through human bone marrow mesenchymal stem cell (hBMSC) directly depositing ECM on surface of scaffolds. However, the role and mechanism of human umbilical cord mesenchymal stem cells (hUCMSC)‐secreted ECM in bone formation remain unknown. We tested the osteoinductive properties of a hUCMSC‐secreted ECM construct ( hUCMSC‐ECM ) in a large femur defect of a severe combined immunodeficiency (SCID) mouse model. The hUCMSC‐ECM improved the colonization of endogenous MSCs and bone regeneration, similar to the hUCMSC‐seeded scaffold and superior to the scaffold substrate. Besides, the hUCMSC‐ECM enhanced the promigratory molecular expressions of the homing cells, including CCR2 and TβRI. Furthermore, the hUCMSC‐ECM increased the number of migrated MSCs by nearly 3.3 ± 0.1‐fold, relative to the scaffold substrate. As the most abundant cytokine deposited in the hUCMSC‐ECM, insulin‐like growth factor binding protein 3 (IGFBP3) promoted hBMSC migration in the TβRI/II‐ and CCR2‐dependent mechanisms. The hUCMSC‐ECM integrating shRNA‐mediated silencing of Igfbp3 that down‐regulated IGFBP3 expression by approximately 60%, reduced the number of migrated hBMSCs by 47%. In vivo, the hUCMSC‐ECM recruited 10‐fold more endogenous MSCs to initiate bone formation compared to the scaffold substrate. The knock‐down of Igfbp3 in the hUCMSC‐ECM inhibited nearly 60% of MSC homing and bone regeneration capacity. This research demonstrates that IGFBP3 is an important MSC homing molecule and the therapeutic potential of hUCMSC‐ECM in bone regeneration is enhanced by improving MSC homing in an IGFBP3‐dependent mechanism. Abstract : IGFBP3 is an important MSC homing molecule and the therapeutic potential of hUCMSC‐ECM in bone regeneration is enhanced by improving MSC homing in an IGFBP3‐dependent mechanism.